Generalization of the Y-differential autotransformer for 12- and 18-pulse converters - de Seixas, FJM; Goncalves, V. A. (Elsevier B.V., 2006)
This work proposes a methodology to generalize the Y-connections for 12- and 18-pulse autotransformers. A single mathematical expression, obtained through simple trigonometric operations, represents all the connections. The proposed methodology allows choosing any ratio between the input and the output voltages. The converters can operate either as step-up or as step-down voltage. To simplify the design of the windings, graphics are generated to calculate the turn-ratio and the polarity of each secondary winding, with respect to the primary winding. A design example, followed by digital simulations, illustrates the presented steps. Experimental results of two prototypes (12 and 18 pulses) are presented. The results also show that high power factor is an inherent characteristic of multi-pulse converters, without any active or passive power factor pre-regulators needs. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ac-dc converter; autotransformers; 12-pulse; 18-pulse; harmonics; power factor correction